Designing reasonable accommodation of the workplace: a new methodology based on risk assessment. - Pigini L; Andrich R; Liverani G; Bucciarelli P; Occhipinti E (Disability & Rehabilitation: Assistive Technology, 2010)
If working tasks are carried out in inadequate conditions, workers with functional limitations may, over time, risk developing further disabilities. While several validated risk assessment methods exist for able-bodied workers, few studies have been carried out for workers with disabilities. This article, which reports the findings of a Study funded by the Italian Ministry of Labour, proposes a general methodology for the technical and organisational re-design of a worksite, based on risk assessment and irrespective of any worker disability. To this end, a sample of 16 disabled workers, composed of people with either mild or severe motor disabilities, was recruited. Their jobs include business administration (5), computer programmer (1), housewife (1), mechanical worker (2), textile worker (1), bus driver (1), nurse (2), electrical worker (1), teacher (1), warehouseman (1). By using a mix of risk assessment methods and the International Classification of Functioning (ICF) taxonomy, their worksites were re-designed in view of a reasonable accommodation, and prospective evaluation was carried out to check whether the new design would eliminate the risks. In one case -- a man with congenital malformations who works as a help-desk operator for technical assistance in the Information and Communication Technology (ICT) department of a big organisation -- the accommodation was actually carried out within the time span of the study, thus making it possible to confirm the hypotheses raised in the prospective assessment.